Patient perspectives on compensation for biospecimen donation. Issue 2 (3rd April 2018) - Allen, Samuel C.; Lohani, Minisha; Hendershot, Kristopher A.; Deal, Travis R.; White, Taylor; Dixon, Margie D.; Pentz, Rebecca D.
ABSTRACT: Background : The purpose of this study was to determine whether biospecimen donors believe they should receive compensation. This is the first study to report biospecimen donors' views on compensation and can potentially improve informed consent and recruitment practices.Methods : Researchers asked patients undergoing surgical removal of tissue to donate biological materials to a biobank; the request was made at their presurgical appointment or in the preoperative clinic of the Emory University Hospital. We interviewed 126 biospecimen donors within 30 days post surgery regarding their perspective on compensation for biospecimen donation.Results : In response to the question "Should you be paid for your participation in the tissue bank?, " 95 (95/126, 75%) participants answered "No." Of these, 55 (55/95, 58%) indicated that donating biological materials should be about altruism, not gaining a monetary reward. Only 11 (11/126, 9%) participants unequivocally believed they should receive compensation, while 14 (14/126, 11%) felt entitled to compensation only under specific circumstances. Eleven (11/14) "Depends" participants indicated that donors should only be compensated when researchers perform for-profit research. Responses varied by race and income level, with whites more likely to not feel entitled to compensation and higher income participants more likely to respond "Depends."Conclusions : The majority of biospecimen donors stated they should not be paid for tissue bank participation. However, a minority believe they should be paid for donating tissue if the tissue is used in revenue-generating projects. These results provide some support for the current biobanking practice of not providing compensation.